2016
DOI: 10.1002/ece3.1897
|View full text |Cite
|
Sign up to set email alerts
|

Hawksbill turtle terra incognita: conservation genetics of eastern Pacific rookeries

Abstract: Prior to 2008 and the discovery of several important hawksbill turtle (Eretmochelys imbricata) nesting colonies in the EP (Eastern Pacific), the species was considered virtually absent from the region. Research since that time has yielded new insights into EP hawksbills, salient among them being the use of mangrove estuaries for nesting. These recent revelations have raised interest in the genetic characterization of hawksbills in the EP, studies of which have remained lacking to date. Between 2008 and 2014, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 74 publications
(184 reference statements)
1
40
2
Order By: Relevance
“…Hawksbills also occasionally nest on the beach of Puerto Lopez, where the government is currently building a cement boardwalk along most of the beach and the impacts the boardwalk may have on hawksbill nesting remain unknown. It is important to point out that recent genetic research has identified Machalilla as a distinct management unit (MU) from MUs located in Central America (n = 3; Gaos et al, 2016). Coupled with apparent differences in size (CCL) and nesting season (Table 2 and Fig.…”
Section: Conservation Challenges and Opportunitiesmentioning
confidence: 98%
“…Hawksbills also occasionally nest on the beach of Puerto Lopez, where the government is currently building a cement boardwalk along most of the beach and the impacts the boardwalk may have on hawksbill nesting remain unknown. It is important to point out that recent genetic research has identified Machalilla as a distinct management unit (MU) from MUs located in Central America (n = 3; Gaos et al, 2016). Coupled with apparent differences in size (CCL) and nesting season (Table 2 and Fig.…”
Section: Conservation Challenges and Opportunitiesmentioning
confidence: 98%
“…Perhaps the most important advances to this field have been made through expanded sample collections that provide key insights informing designation of units to conserve on a global scale, such as Evolutionary Significant Units (ESUs), Distinct Population Segments (DPSs), and Regional Management Units (RMUs; see Box 2, Table 1 for definitions and applications of conservation units). As sample coverage continues to improve for all species in parallel with better analytical tools, marine turtle studies continue to explore questions of past glacial refuges (e.g., Hamabata et al, 2013;Naro-Maciel et al, 2014a), colonization routes (Dutton et al, 2014a;Shamblin et al, 2014;Gaos et al, 2016), and multiple colonization events that create such complexity in marine turtle phylogeographic patterns (e.g., Dethmers et al, 2006;Vargas et al, 2016). The field of marine turtle phylogeography will undoubtedly continue to advance in coming years with the development of genomic approaches and novel analytical tools.…”
Section: Evolutionary History and Phylogeographymentioning
confidence: 99%
“…• How isolated or connected are rookeries from one another through the exchange of nesting females? Population structure analyses of nesting females across regions of interest (mtDNA haplotypes and/or fine-scale nuclear markers a ) Examples since comprehensive review in Jensen et al (2013a) include: Dutton et al (2014b), Shamblin et al (2014), Vargas et al (2016), Gaos et al (2016), and Matsuzawa et al (2016) • How does male-mediated gene flow influence population structure among rookeries? Population structure analyses, various methods including: sampling nesting females, hatchlings and/or males in-water at breeding grounds (fine-scale nuclear markers; mtDNA haplotypes under specific circumstances b ) Wallace et al (2010b); references for information specific to each species is listed within the table.…”
Section: How Are Rookeries Connected To Each Other and Linked To Foramentioning
confidence: 99%
See 1 more Smart Citation
“…Fontaine et al 2007, Martien et al 2014, Viricel & Rosel 2014, Gaos et al 2016. Many potential drivers of population structure within the marine realm have been identified, including resource and habitat specialization, physiographic and oceanographic barriers, and social organizations that limit gene flow between groups.…”
Section: Introductionmentioning
confidence: 99%